(untitled) (GAIMS Journal of Medical Sciences, 2023)
Background: Autopsy plays a vital role in identifying the cause and time of death. It also aids in understanding the emerging trends and pathogenesis in the course of the diseases and its consequences which leads to death. The aim of this study was to study the cardiac pathologies encountered during the histopathological examination in the autopsied heart specimens. Methodology: We did a cross sectional retrospective study on heart specimens received in the Department of Pathology, Government Royapettah Hospital, Kilpauk Medical College, Chennai for a period of 3 years from 2020 to 2022. Results: Out of 291 autopsy cases received during this period, 170 well preserved hearts obtained from medicolegal autopsies were studied. In this study 67% were males and 33% were females. In the current study we found that atherosclerosis and coronary artery disease are the most common findings. The most common coronary artery exhibiting atherosclerotic change was left anterior descending artery. An array of cases with rare cardiac pathologies such as giant cell myocarditis, hypoplastic left heart syndrome, infective endocarditis, hypertrophic cardiomyopathy, ventricular aneurysm and metastatic deposits in the heart were highlighted in the current study. Conclusions: With the help of histopathological findings, the present study has contributed to a range of rare lesions in cardiac pathology determining the cause of death which were not diagnosed antemortem. Thus, this study emphasizes on the essentiality and multidisciplinary approach of postmortem histopathological examination in determining the causative factor of the disease significant enough to change the course of the disease if recognized before death.